Semarang Ragam Inspirasi dalam Memperingati Hari Anak Nasional Kota Semarang (Talkshow, Ragam Lomba Anak, Pentas Seni Daring, Webinar, Konser Amal, Donasi) Sebagai Project Leader, Koordinator Webinar, Koordinator Sponsorship - Ahdani Gita Sadida; Djoko Setyabudi (Interaksi Online, 2021)
National Children's Day is the day the rights of Indonesian children are fulfilled, both for children who are in Indonesia and for children who are outside Indonesia. Every year the commemoration of National Children's Day is held through various activities for children. All national groups, both from the government and the private sector, participate in commemorating National Children's Day starting from the Central, Provincial, to all Regencies / Cities. In this case, Indonesia is currently experiencing a Covid-19 pandemic which has an impact on all community activities to develop. One of them is Semarang City, which is to commemorate National Children's Day 2020, the City of Semarang in particular the Semarang City Women Empowerment and Child Protection Service (DP3A) as the implementing committee is collaborating with the Semarang City Social Service to make National Children's Day successful in Semarang City during this pandemic. There are 6 activities namely Talkshow, Variety of Children's Contest, Online Art Performance, Webinar, Charity Concert, Donation. These activities will be carried out online and offline but still adhere to health protocols. The series of activities began on July 14, 2002 to August 18, 2020. After being held at that time there were more than 800 students who took part in the art show, from the previous target of 300 students, there were 15 media partners who were among the 10 determined targets, reaching the presence of resource persons. for talk shows and webinars, reaching 150 participants, and for donations reaching Rp. 14. 954,250 from the previous target of Rp. 5,000,000.